Is the United States Still Dominant in the Global Pharmaceutical Innovation Network? - Hu, Yuanjia; Scherngell, Thomas; Man, Si Nga; Wang, Yitao (PLOS ONE, 2013)
The dramatic growth of research and development activities in the pharmaceutical sector in emerging economies raises the question of whether the United States still keeps its dominant role in the global pharmaceutical innovation landscape. This paper focuses on investigating the role of the United States in global pharmaceutical innovation, and differs from previous studies by shifting attention to a network analytic perspective to track the global distribution of pharmaceutical inventions. Our sample is composed of key patents covering all new drugs approved by the Food and Drug Administration between 1996 and 2010. The results show that the United States still dominates in the global pharmaceutical innovation network, especially when it comes to essential core inventions. However, the United States shows a slightly decreasing prominence in the networks of either total new drugs or New Molecular Entity (NME) drugs in the time period 2006–2010 as compared to previous time periods, revealed by subtle traces of network centralities.